Importance of the forensic dentist in criminal forensics: analysis of a human bite mark in a homicide case (Research, Society and Development, 2021)
Objective: To demonstrate, by means of a case report, the importance of the presence of dental experts in the officials institutes of expertise for the correct analysis of the traces of bite marks. Case Report: A corpse was admitted in an official forensic institution in Northeastern Brazil, victim of a fire gun. This patient had a lesion on the left side of the arm, deltoid region, compatible with a human bite mark. Thus, photographs and drawings were made on an acetate sheet overlapped on the lesion for a future comparison. One month after the necroscopic examination, a suspicion was brought to the expert institute for tests to collect parameters for the confrontation of the dental arch, which included photographs, bite marks in wax sheet, models in plaster and measurements of the dental elements. After the confrontation, several points were found to coincide in both arches, with no signs of divergence. Conclusion: The assignment of the dental expert transcends necroscopic examinations: his expertise is essential in cases involving human bites, being a strong ally of justice to ascertain the truth. What, in this case, by the methodologies used, became evident when it came to identifying the authorship of the bite mark due to the absence of contradictions and the remarkable compatibility between the bite mark found and the arches of the suspect.